Human Rights: Body Checking Paradox of Miss Universe Indonesia 2023 Finalist - Nuraziza Utami , Denissa; Rahmawati, Regina Putri; Sadira Karimah , Farah (Hasanuddin Journal of Sociology (HJS), 2024)
Every living creature has the same rights, namely the right to life, the right to express opinions, and the right to equal equality before the law. These rights are called Human Rights (HAM) which will provide protection for every individual living in a region or country. Governments and institutions that are closely related to human rights can always be obliged to protect their people. One of the cases of human rights violations was in the Miss Universe Indonesia beauty contest which will be held in 2023. The violations committed were in the form of sexual violence through body checking procedures. The aim of this research is to examine human rights violations that occurred in the Miss Universe Indonesia 2023 beauty pageant. This research uses a literature study approach or collects information related to data in the form of articles and journals in previous research. The case of human rights violations in the Miss Universe Indonesia 2023 beauty pageant requires special attention, namely by maximizing the role of the Ministry of Women's Empowerment and Child Protection.